Implikasi Pendidikan dari Q.S Hud 42-46 tentang Kisah Kan’an Bin Nuh AS terhadap Pendidikan Akhlak Anak - Abdurrahman, Muhammad Nabhan; Asikin, Ikin; Mulyani, Dewi (UNISBA Press, 2024)
Abstract. Moral education for children is very important. If parents do not properly educate or pay attention to them, children will grow up with poor morals. This phenomenon is characterized by a moral crisis, especially in children, which is still affecting all around us, namely mazmumah morals. This research aims to develop good characteristics in children towards their parents. The research method used is a descriptive analysis method and a qualitative approach using library research techniques and analysis of tafsir books. Accompanied by a survey of literature related to the problem observed. The author uses the tahlili interpretation method, namely explaining the meaning of mufradat and sentences and identifying the opinions of the mufassirs. The results of this research from Q.S Hud 42-46 are the implications of moral education for children which include: Disobedience and arrogance do not benefit the perpetrator, Religious ties are stronger than hereditary ties and have no relationship to the piety and piety of descendants, Instilling the values of aqidah will lead to knowing who its creator is. what is their religion and what they must believe in? By example, for children who are used to imitating the good habits of their parents, children will easily imitate good things. Instilling and cultivating moral educational values in children is very necessary for parents, so that a child has good characteristics, especially morals towards parents. Providing moral learning to children from an early age will create habits in the future. as is the lesson that can be taken from Q.S Hud 42-46 about the story of Kan'an Bin Nuh AS so that parents pay more attention to the moral education of their children. Abstrak. Pendidikan akhlak terhadap anak sangat penting. Jika tidak dididik atau diperhatikan secara benar oleh para orang tua, maka nantinya anak tumbuh dalam keadaan akhlak yang kurang baik. Fenomena ini ditandai dengan krisis akhlak, khususnya pada anak yang sampai sekarang ini masih melanda disekitar kita yaitu akhlak mazmumah. penelitian ini bertujuan untuk menumbuhkan karakteristik anak dengan baik terhadap orang tua. Metode penelitian yang digunakan adalah metode deskriptif analisis dan pendekatan kualitatif dengan menggunakan teknik library research dan menggunakan analisis pada kitab-kitab tafsir. Disertai dengan survei terhadap literatur yang berkaitan dengan masalah yang diamati. penulis menggunakan metode tafsir tahlili yaitu menjelaskan makna mufradat dan kalimat serta mengidentifikasi pendapat para mufassir. Hasil penelitian dari Q.S Hud 42-46 ini yaitu implikasi pendidikan akhlak bagi anak yang meliputi Pembangkangan dan kesombongan tidak mendapatkan manfaat bagi pelakunya, Ikatan agama lebih kuat ketimbang ikatan keturunan dan tak ada hubungan bagi kesalehan dan ketakwaan keturunan, Menanamkan nilai akidah akan mengenal siapa penciptanya apa agamanya dan apa saja yang wajib diimaninya, Keteladanan bagi anak yang terbiasa meniru kebiasaan baik orang tua maka anak akan mudah meniru hal-hal baik. Menanamkan dan menumbuhkan nilai-nilai pendidikan akhlak pada anak sangat diperlukan oleh orang tua, agar seorang anak memiliki karakteristik yang baik terutama akhlak terhadap orang tua. Memberikan pembelajaran akhlak kepada anak sejak dini akan menjadikan pembiasaan dimasa yang akan datang. sebagaimana pembelajaran yang bisa diambil dalam Q.S Hud 42-46 tentang kisah Kan'an Bin Nuh AS agar orang tua lebih memperhatikan pendidikan akhlak terhadap anak-anaknya.